2015
DOI: 10.1111/jocn.12749
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilisation by critically ill older patients following an intensive care unit stay

Abstract: Adequate healthcare resources, such as facilitated access to medical follow-up care, rehabilitation programs and home healthcare services, must be easily accessible for older patients following hospital discharge. Nurses need to be aware of the healthcare services available and advise patients accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(76 reference statements)
0
5
0
1
Order By: Relevance
“…[18] One study of critically ill older patients with a matched control group also reported more general practitioner consultations and higher medication intake for post-ICU subjects. [47] In contrast, another cohort study of post-ICU patients found no change in the number of general practitioner consultations or medications in the majority of the participants. [48]…”
Section: Discussionmentioning
confidence: 99%
“…[18] One study of critically ill older patients with a matched control group also reported more general practitioner consultations and higher medication intake for post-ICU subjects. [47] In contrast, another cohort study of post-ICU patients found no change in the number of general practitioner consultations or medications in the majority of the participants. [48]…”
Section: Discussionmentioning
confidence: 99%
“…ICU follow-up care has been suggested as a potential means to address the physical, cognitive and mental problems faced after discharge, but it is unknown which (combination of) interventions are most (cost)effective [7, 8]. Studies proposed that frequent visits to GPs allowed early recognition and proactive treatment of health problems that prevented further hospitalizations [28] and that the post-hospital collaboration among hospital, GP and community services regarding physical and neuropsychological rehabilitation should be strengthened [26]. A multi-centre study conducted in the Netherlands reported that, at three months after discharge, almost 70% of the ICU survivors had had contact with the GP.…”
Section: Discussionmentioning
confidence: 99%
“…GPs should be extra alert after critical illness and use their holistic approach to diagnose or prevent possible symptoms in all three domains of PICS (physical, mental and cognitive). For this reason, GPs play a pivotal role in post-ICU care, as frequent visits to GPs might lead to early recognition and treatment [ 37 ]. Thereby, collaboration after hospital discharge among primary care, hospitals and community services should be strengthened [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%